Comparative analysis of lens structural changes in ex-clean-up workers exposed to radiation from Chornobyl versus non-exposed individuals (Ukrainian Journal of Ophthalmology, 2024)
Purpose. The purpose of this research was to measure lens posterior cortex thickness and compare it between Chornobyl ex-clean-up workers and healthy individuals to determine whether Chornobyl ex-clean-up workers have a higher prevalence of posterior cortex cataract.Methods. The study was conducted on 32 eyes of healthy, non-exposed individuals, 32 eyes of individuals who worked only in Chornobyl City, and 16 eyes of individuals who worked on the roof of the reactor. All measurements were performed using a Heidelberg Anterion device. Statistical analyses were performed using Jamovi statistical software.Results. The results showed that those who had worked on the roof of the reactor had a significantly higher percentage of their lens occupied by the posterior cortex (median 17.3%, IQR 15.5–18.5%) compared to both the controls and city workers. Therefore, they also have a higher prevalence of posterior subcapsular cataracts (p
Keywords: Ionising radiation; nuclear power plant; radiation accident; cataract